Efficient agglomerative hierarchical clustering. Issue 5 (1st April 2015) - Bouguettaya, Athman; Yu, Qi; Liu, Xumin; Zhou, Xiangmin; Song, Andy
Highlights An efficient hybrid hierarchical clustering is proposed based on agglomerative method. It performs consistently with different distance measures. It performs consistently on data with different distributions and sizes.